Kirigami Reconfigurable Gradient Metasurface (Adv. Funct. Mater. 5/2022). (25th January 2022) - Zheng, Yilin; Chen, Ke; Yang, Weixu; Wu, Linxiao; Qu, Kai; Zhao, Junming; Jiang, Tian; Feng, Yijun
Abstract : Reconfigurable Gradient Metasurfaces Kirigami, the ancient art of paper cutting, has recently been widely studied in modern science and technology. In article number 2107699, Ke Chen, Yijun Feng, and co‐workers use 3D kirigami configurations to achieve reconfigurable gradient metasurfaces. This concept combines continuous functional variation with structural self‐folding and develops a series of electromagnetic meta‐devices including a reconfigurable anomalous refractor, tunable focusing metalens, and achromatic metalens.